2020
DOI: 10.1002/aelm.202000793
|View full text |Cite
|
Sign up to set email alerts
|

High‐Efficiency Spin–Orbit Torque Switching Using a Single Heavy‐Metal Alloy with Opposite Spin Hall Angles

Abstract: Spin–orbit torque (SOT) induced perpendicular magnetization switching in Pt1‐xGdx/Co/Al2O3 heterostructure with x = 0, 0.02, 0.14, 0.30, and 0.33 is investigated. With in‐plane charge current flowing through the Pt1‐xGdx layer, field‐free current‐induced magnetization switching is observed for all nonzero x due to the existence of opposite spin Hall angles (θSHA) from Pt1‐xGdx alloys. Furthermore, the large θSHA of about 0.27 is obtained in the optimal Pt0.70Gd0.30 alloy films, which is about four times larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 52 publications
1
37
0
2
Order By: Relevance
“…This is exploited to switch the magnetization of an attached layer of Co by SOT. [44] According to our results, a GdFeCo/Cu bilayer should be even more effective for the global generation of spin current, SHE-like plus SAHE-like. We also suggest that the switching of a magnetic layer deposited on GdFeCo/Cu could take advantage not only on the intensity of the spin current emission by GdFeCo/Cu but also on the combination of torques of different symmetries.…”
Section: Effsupporting
confidence: 53%
See 1 more Smart Citation
“…This is exploited to switch the magnetization of an attached layer of Co by SOT. [44] According to our results, a GdFeCo/Cu bilayer should be even more effective for the global generation of spin current, SHE-like plus SAHE-like. We also suggest that the switching of a magnetic layer deposited on GdFeCo/Cu could take advantage not only on the intensity of the spin current emission by GdFeCo/Cu but also on the combination of torques of different symmetries.…”
Section: Effsupporting
confidence: 53%
“…This is a unique information of what can be the relative proportions of the SAHE-like and SHElike symmetries in a magnetic material, respectively about 80% and 20% for the spin currents emitted by GdFeCo/Cu (overall, including bulk and interfacial contributions). We note here that a very recent work [44] has shown the remarkably efficient generation of spin current by other Gd alloys. In GdPt alloys, the corresponding θ SHE reaches values around 0.27, well above the θ SHE of Pt.…”
Section: Effmentioning
confidence: 61%
“…[5][6][7] The conventional SOT-based MTJ device is composed of the MTJ device deposited above a nonmagnetic heavy metal (HM) layer. [7][8][9] The writing current flows through the low resistance HM layer rather than directly through the MTJ junction, [9][10][11] thereby increasing the opportunity to improve the read stability and energy consumption. These advantages make SOT-MRAM has much better endurance and is considered as the next-generation non-volatile memory.…”
Section: Tuning the High-efficiency Field-free Current-induced Deterministic Switching Via Ultrathin Ptmo Layer With Mo Contentmentioning
confidence: 99%
“…However, SOT-driven perpendicular magnetization switching generally requires an additional in-plane magnetic field for symmetry breaking, which is a great obstacle for the integration of an in-plane field source into the nanodevices, and it is undesirable for scaling down and practical applications. [11][12][13][14] By far, many approaches have been proposed for attaining a scalable field-free SOT-driven perpendicular magnetization switching such as by substituting the HM with antiferromagnets (AFM) layers like PtMn and IrMn, [12,[15][16] through the localized laser annealing, [17] by interlayer exchange coupling (IEC), [8,[18][19][20] through electric field control method, [21][22] or by an electrically generated strain. [23] Ma et al [24] reported the field-free SOT-driven magnetization switching by competing spin currents via a bilayer made of HMs with opposite spin Hall angles (θ SHA ).…”
Section: Tuning the High-efficiency Field-free Current-induced Deterministic Switching Via Ultrathin Ptmo Layer With Mo Contentmentioning
confidence: 99%
See 1 more Smart Citation